Differential Morphophysiological and Biochemical Responses of Cotton Genotypes Under Various Salinity Stress Levels During Early Growth Stage - Munawar, Wajeeha; Hameed, Amjad; Khan, Muhammad Khashif Riaz (Frontiers in Plant Science, 2021)
Cotton is a primary agriculture product important for fiber use in textiles and the second major oil seed crop. Cotton is considered as moderately tolerant to salt stress with salinity threshold of 7.7 dS/m at seedling stage. Salinity causes reduction in the growth of seedlings and cotton production that limits fiber quality and cotton yield. In this study, initially, 22 cotton genotypes were screened for relative salt tolerance using germination test in Petri plates (growth chamber). Selected 11 genotypes were further tested in pot experiment (sand) with 0, 15, and 20 dS/m NaCl treatments under glass house conditions. At four-leaves stage, different morphological and physiological traits were measured for all genotypes while biochemical analysis was performed on selected seven highly tolerant and sensitive genotypes. NaCl treatment significantly reduced plant biomass in two genotypes IR-NIBGE-13 and BS-2018, while NIAB-135, NIAB-512, and GH-HADI had least difference in fresh weight between the control and NaCl-treated plants. Photosynthetic rate was maintained in all the genotypes with the exception of SITARA-16. In two sensitive genotypes (IR-NIBGE-13 and 6071/16), Na+ ion accumulated more in leaves as compared to K+ ion under stress conditions, and an increase in Na+/K+ ratio was also observed. The lesser accumulation of malondialdehyde (MDA) content and higher activity of enzymatic antioxidants such as superoxide dismutase (SOD), peroxidase (POD), and ascorbate peroxidase (APX) in stressed plants of NIAB-135, NIAB-512, and FH-152 indicated that these genotypes had adaption capacity for salinity stress in comparison with sensitive genotypes, i.e., IR-NIBGE-13 and 6071/16. The observed salt tolerance was corelated with plant biomass maintenance (morphological), photosynthetic rate, and ionic homeostasis (K+/Na+ ratio, physiological) and biochemical stress marker regulations. After a series of experiments, it was concluded that NIAB-135, NIAB-512, and FH-152 could be utilized in breeding programs aimed at improving salinity tolerance in cotton and can expand cotton cultivation in saline area.